How to Approach Public Services Based on Social Inclusion for Marginalized Communities? Bibliometric Analysis and Literature Review - Tahir, Nurbiah; Ibrahim, Muh. Akmal (KnE Social Sciences, 2025)
Social inclusion-based public services emphasize access, participation, and equitable treatment for all segments of society, particularly for marginalized groups such as women, people with disabilities, the poor, the elderly, and minority communities. Governments play a strategic role in designing and implementing policies that are responsive to the needs of these vulnerable groups through fair, equal, and sustainable services. This study aims to explore ways of improving inclusive public services and to map the development of related research through a literature review and bibliometric analysis. The methodology includes a systematic literature review of scholarly articles published between 1997 and 2025, sourced from the Scopus database. The analysis is conducted using bibliometric methods with tools such as VOSviewer and Biblioshiny (RStudio) to identify research trends, key terms, author collaborations, and citation networks. The findings highlight the significant role of co-production in addressing issues related to gender, disability, and children by involving these groups in the design and management of public services. In terms of gender, co-production allows women, especially those from marginalized backgrounds, to participate in decision-making processes, ensuring policies are more responsive to their needs. For people with disabilities, it promotes the development of services that are inclusive and accessible. Children, who are often excluded from policy discussions, can also be engaged in shaping services such as education and child protection, making these more attuned to their rights and welfare. Thus, co-production fosters more inclusive, participatory, and equitable public service delivery.